Intervening to Enhance Proactivity in Organizations: Improving the Present or Changing the Future - Strauss, K.; Parker, Sharon (Sage Publications, Inc., 2018)
A growing body of evidence has linked proactivity at work to positive outcomes. Yet little research to date has investigated whether employees’ proactive behavior in organizations can be facilitated through training and development. Nor has research considered which variables shape employees’ responses to such interventions. We investigate the effects on proactivity of two theoretically distinct training and development interventions in a randomized field experiment with police officers and police support staff (N = 112). We hypothesized that a problem-focused intervention, which made discrepancies between the status quo and the ideal present more salient, would lead to increases in individual task proactivity, whereas a vision-focused intervention, which made discrepancies between the status quo and an ideal future more salient, would increase organization member proactivity. Intervention effects were moderated by role overload and future orientation, respectively. Only individuals with high levels of role overload increased their individual task proactivity as a result of the problem-focused intervention, and only individuals high in future orientation increased their organization member proactivity as a result of the vision-focused intervention. Our study integrates different cybernetic perspectives on how proactivity is motivated and provides novel insights into moderators of interventions designed to capture these different mechanisms. From a practical perspective, our study supports organizations seeking to implement training and development interventions and helps them to determine who might benefit most from interventions.